2011
DOI: 10.1371/journal.pone.0017881
|View full text |Cite
|
Sign up to set email alerts
|

Design of Glycopeptides Used to Investigate Class II MHC Binding and T-Cell Responses Associated with Autoimmune Arthritis

Abstract: The glycopeptide fragment CII259–273 from type II collagen (CII) binds to the murine Aq and human DR4 class II Major Histocompatibility Complex (MHC II) proteins, which are associated with development of murine collagen-induced arthritis (CIA) and rheumatoid arthritis (RA), respectively. It has been shown that CII259–273 can be used in therapeutic vaccination of CIA. This glycopeptide also elicits responses from T-cells obtained from RA patients, which indicates that it has an important role in RA as well. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 82 publications
(96 reference statements)
1
29
1
Order By: Relevance
“…The C-terminus on the other hand proved to be much more flexible and did not adopt a stable binding mode during the course of the simulations. This is consistent with previous MD simulations of the system, 10,13 as well as the fact that the minimal epitope required for binding to A q consists of the N-terminal octapeptide Ile 260 -Gln 267 . 7 The S-and R-hydroxyethylene-isosteric glycopeptides 2 and 3 displayed a different dynamic pattern compared to 1, with large variations between the repeated MD simulations (Table 1 and ESI †).…”
Section: Flexibility Of Glycopeptide Binding To a Qsupporting
confidence: 92%
See 2 more Smart Citations
“…The C-terminus on the other hand proved to be much more flexible and did not adopt a stable binding mode during the course of the simulations. This is consistent with previous MD simulations of the system, 10,13 as well as the fact that the minimal epitope required for binding to A q consists of the N-terminal octapeptide Ile 260 -Gln 267 . 7 The S-and R-hydroxyethylene-isosteric glycopeptides 2 and 3 displayed a different dynamic pattern compared to 1, with large variations between the repeated MD simulations (Table 1 and ESI †).…”
Section: Flexibility Of Glycopeptide Binding To a Qsupporting
confidence: 92%
“…2). 9,10 Moreover, the galactosylated hydroxylysine at position 264 protrudes out of the binding site and is recognized by the TCR with exquisite specificity. 11 Modification of glycopeptides, through the incorporation of amide bond isosteres, has been used to probe molecular interactions in the MHC/glycopeptide/TCR system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By employing a panel of synthetic glycopeptides, it was found that most T-cell hybridomas obtained in collagen-induced arthritis specifically recognize a β- D -galactopyranoside moiety located at Hyl264 of the peptide sequence CII256–270 (refs. 65,66). Further studies showed that the axial hydroxyl group of the galactoside was critical for T-cell activation.…”
Section: Glycopeptides and Antigen Presentation And T-cell Primingmentioning
confidence: 99%
“…2) were attempted to access their inhibitory efficacy on changing chemical states of termini. It has also been reported that glycopeptides could be used as therapeutic agent to design a vaccine [131] and a novel ligand [132]. Therefore, addition of glucose and deoxyglucose fragments was also considered to make IGD tripeptide specific to tumor cells, which have a high demand for glucose [133].…”
Section: De Novo Designing Of Igd As Novel Bcl-2 Inhibitorsmentioning
confidence: 99%